Abolishing School Fees in Africa : Lessons from Ethiopia, Ghana, Kenya, Malawi, and Mozambique - World Bank (World Bank, 2012)
This book constitutes one of the main outputs of the School Fee Abolition Initiative (SFAI). The initiative, launched in 2005 by the United Nations Children's Fund (UNICEF) and the World Bank, was designed to support countries in maintaining and accelerating progress toward universal primary education as outlined in the Millennium Development Goals and the Education for All (EFA) goals. Specifically, SFAI strengthens country efforts to eliminate school fees and/or implement targeted exemptions, subsidizations, and incentives to reduce education costs for the poor. The initiative has now grown into a broad partnership through the involvement of other key development partners and constituencies as well as research and academic institutions. SFAI promotes access to quality basic education worldwide through three specific and interlinked goals. The first is to construct a knowledge base on school fee abolition in order to inform sound and sustainable policies, strategies, and interventions. SFAI recognizes that school fee abolition is a complex process that requires both the development of a credible database and the solid analysis that builds on lessons learned from experience. The second goal is to provide guidance and support to countries in planning and implementing school fee abolition policies. Engagement by SFAI partners is taking the form of both technical and financial assistance within the framework of ongoing national planning processes. The third goal is to advance the global policy dialogue on the financial barriers to education access and to build on existing EFA partnerships. The result will ensure a good understanding of the complexities involved in school fee abolition, facilitate the articulation of complementary roles, and create an environment for success.